Mapping the Degradable Kinome Provides a Resource for Expedited Degrader Development - Donovan, Katherine A; Ferguson, Fleur M; Bushman, Jonathan W; Eleuteri, Nicholas A; Bhunia, Debabrata; Ryu, SeongShick; Tan, Li; Shi, Kun; Yue, Hong; Liu, Xiaoxi; Dobrovolsky, Dennis; Jiang, Baishan; et al. (Cell, 2020)
Targeted protein degradation (TPD) refers to the use of small molecules to induce ubiquitin-dependent degradation of proteins. TPD is of interest in drug development, as it can address previously inaccessible targets. However, degrader discovery and optimization remains an inefficient process due to a lack of understanding of the relative importance of the key molecular events required to induce target degradation. Here, we use chemo-proteomics to annotate the degradable kinome. Our expansive dataset provides chemical leads for ∼200 kinases and demonstrates that the current practice of starting from the highest potency binder is an ineffective method for discovering active compounds. We develop multitargeted degraders to answer fundamental questions about the ubiquitin proteasome system, uncovering that kinase degradation is p97 dependent. This work will not only fuel kinase degrader discovery, but also provides a blueprint for evaluating targeted degradation across entire gene families to accelerate understanding of TPD beyond the kinome.